Understanding the structural and dynamic consequences of DNA epigenetic modifications: Computational insights into cytosine methylation and hydroxymethylation - Carvalho, Alexandra T P (Epigenetics, 2015)
We report a series of molecular dynamics (MD) simulations of up to a microsecond combined simulation time designed to probe epigenetically modified DNA sequences. More specifically, by monitoring the effects of methylation and hydroxymethylation of cytosine in different DNA sequences, we show, for the first time, that DNA epigenetic modifications change the molecule's dynamical landscape, increasing the propensity of DNA toward different values of twist and/or roll/tilt angles (in relation to the unmodified DNA) at the modification sites. Moreover, both the extent and position of different modifications have significant effects on the amount of structural variation observed. We propose that these conformational differences, which are dependent on the sequence environment, can provide specificity for protein binding.